2022
DOI: 10.3390/foods11223624
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 11 Mycotoxins in Maize via Multiple-Impurity Adsorption Combined with Liquid Chromatography–Tandem Mass Spectrometry

Abstract: In this study, multiple-impurity adsorption purification (MIA) technologies and liquid chromatography–tandem mass spectrometry (LC-MS/MS) were used to establish a method for detecting 11 mycotoxins in maize. The conditions for mass spectrometry and MIA were optimized. Maize was extracted with 70% acetonitrile solution, enriched, and purified using MIA technologies, and then, analyzed via LC-MS/MS. The results showed that the linear correlation coefficients of the 11 mycotoxins were >0.99, the sample recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A further advantage for the use of LC-HRMS is that the confirmation of analytes can be performed through the use of databases. Some examples of the use of LC-HRMS for T-2 and HT-2 include the studies by Tamura et al [123] and Romera et al [157]. The former analysed 20 Fusarium toxins in cereals including barley, using an LC-Orbitrap MS with a two-step clean-up, which included the use of QuEChERs followed by purification using a Multistep 229 Ochra multifunctional cartridge.…”
Section: Confirmatory Analysismentioning
confidence: 99%
“…A further advantage for the use of LC-HRMS is that the confirmation of analytes can be performed through the use of databases. Some examples of the use of LC-HRMS for T-2 and HT-2 include the studies by Tamura et al [123] and Romera et al [157]. The former analysed 20 Fusarium toxins in cereals including barley, using an LC-Orbitrap MS with a two-step clean-up, which included the use of QuEChERs followed by purification using a Multistep 229 Ochra multifunctional cartridge.…”
Section: Confirmatory Analysismentioning
confidence: 99%
“…In 1993, the International Agency for Research on Cancer (IARC) classified OTAs as Class 2B carcinogens. Relevant studies have shown that when infants eat OTA contaminated breast milk, their own immune system is damaged, unable to degrade toxins, and they may suffer from kidney disease and various types of cancer [3] .…”
Section: Ochratoxinmentioning
confidence: 99%
“…Despite this situation, the literature on Fusarium in wheat is about three-fold greater than that in maize. An increasing amount of information has indicated that multi-toxin contamination is a serious food safety challenge; as such, research should be urgently conducted to provide solutions to keep such contamination under control [2].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the starch part was much less contaminated. Guan et al [2] checked 11 mycotoxins, and, beyond the regular AFs, DON, FBs, and ZEN, OTA was also identified. Eckhard et al [92] observed DON in every silo maize sample, but (in decreasing order) nivalenol, T-2, HT-2, acetylated DON, and FBs were also detected.…”
mentioning
confidence: 99%